2006
DOI: 10.1515/cclm.2006.054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hemolysis on routine clinical chemistry testing

Abstract: If hemolysis and blood cell lysis result from an in vitro cause, we suggest that the most convenient corrective solution might be quantification of free hemoglobin, alerting the clinicians and sample recollection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
194
4
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(226 citation statements)
references
References 20 publications
9
194
4
19
Order By: Relevance
“…In addition, an arbitrary threshold of free hemoglobin measured by the cyanmethemoglobin method was established at 0.6 g/L. This concentration of free hemoglobin is suggestive of a mildly hemolyzed specimen and represents the threshold for deciding whether some test results might already be significantly affected by in vitro hemolysis (e.g., aspartate aminotransferase, lactate dehydrogenase and potassium) (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an arbitrary threshold of free hemoglobin measured by the cyanmethemoglobin method was established at 0.6 g/L. This concentration of free hemoglobin is suggestive of a mildly hemolyzed specimen and represents the threshold for deciding whether some test results might already be significantly affected by in vitro hemolysis (e.g., aspartate aminotransferase, lactate dehydrogenase and potassium) (8).…”
Section: Methodsmentioning
confidence: 99%
“…The interference effect from hemolysis in laboratory diagnostics is a consequence of several coexisting biological and analytical causes, including (a) leakage of hemoglobin and other intracellular components into the surrounding fluid thereby producing false elevations of intracellular analytes or dilutional effects, (b) method-and analyte-dependent spectrophotometric interferences and (c) chemical interference in a variety of analytic reactions. At high concentrations of serum hemoglobin, all these interference effects might coexist, thereby producing spurious variations that do not necessarily follow the same pattern resulting in overestimation or underestimation (1,2,7,8). The magnitude of this problem is further magnified by the management of hemolytic specimens in the laboratory, from their identification to the optimal means of handling them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTA samples were maintained at room temperature and analyzed within 60 minutes. Because hemolysis falsely increases serum iron in people,18 any sample with gross evidence of hemolysis in either the plasma or serum was redrawn. Sera were harvested and frozen at −20°C for a maximum of 4 days and shipped overnight on dry ice to the Kansas State University Comparative Hematology Laboratory for measurement of serum iron, serum ferritin, and TIBC.…”
Section: Methodsmentioning
confidence: 99%
“…The drawbacks of only using plasma glucose for diagnosing diabetes are well known to most working in the field of laboratory diagnostics, and are mainly attributable to the high vulnerability of this test to preanalytical variables, especially to the storage conditions and the presence of spurious hemolysis [12]. This is also reflected by the recent findings of Nielsen et al, who showed that the percentage of undiagnosed patients with diabetes may be reduced by approximately 2% with replacement of fasting plasma glucose with HbA 1c [13].…”
mentioning
confidence: 99%